Roman ceramics from Fabrateria Nova: New perspectives on the relationships between the city and its hinterland through the analysis of ceramic assemblages - Manzini, Ilaria; P. Venditti, Caterina (Rei Cretariae Romanae Fautorum Acta, 2017)
Ceramic finds presented hereby were recovered during excavations at the “Civita” plateau of San Giovanni Incarico (Lazio, Italy). The plateau corresponds to the site of the ancient Fabrateria Nova, an urban centre established on a broad terrace enclosed by the River Liri in 124 BC, i.e. one year after the destruction of the nearby and better known city of Fregellae.